2012
DOI: 10.1155/2012/503023
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Executive Functions in a Real-Life Setting: Goal Management Training Applied to a Person with Schizophrenia

Abstract: The aim was to assess the efficacy of a modified version of Goal Management Training (GMT) in a person with schizophrenia who had difficulties in attaining the final goal for new and multitasking daily-life situations. GMT is designed to improve abilities in establishing goal-directed plans and carrying them out effectively. Beneficial effects of GMT were measured for several clinical questionnaires, laboratory tasks, and three real-life situations: meal preparation (trained, familiar); washing (nontrained, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…The MPT (Levaux, Larøi, et al ., ; Levaux, Van der Linden, et al ., ) is a real‐life activity task designed to take into account the complex, multitasking nature of unfamiliar everyday life activities. Participants are required to prepare a room for a meeting that nine people (a manager, a secretary, and seven guests) will attend.…”
Section: Methodsmentioning
confidence: 98%
“…The MPT (Levaux, Larøi, et al ., ; Levaux, Van der Linden, et al ., ) is a real‐life activity task designed to take into account the complex, multitasking nature of unfamiliar everyday life activities. Participants are required to prepare a room for a meeting that nine people (a manager, a secretary, and seven guests) will attend.…”
Section: Methodsmentioning
confidence: 98%
“…However, as encouraging as those data are, long-term maintenance of improvement is typically not assessed. Actually, only one case report (i.e., 2 years: Levaux et al, 2012) and one group-based GMT (i.e., 2 years: Loya et al, 2017) study have reported followup analyses more than 7 months post-intervention, limiting the evidence for long-term effects. In the study by Loya et al's (2017), 16 participants with ABI were interviewed by phone 20 months following completion of a multifaceted intervention with elements from GMT (Goal-Oriented Attentional Self-Regulation (GOALS) training).…”
Section: Introductionmentioning
confidence: 99%
“…This concept can also contribute to novel remedial methods, as some data suggest that programs focusing on goal-directed behaviors, such as individualized Goal Management Training, can help people with schizophrenia to manage everyday issues in a sustainable manner. 53 Thus, we believe that further investigation of goal-directed behaviors in patients with schizophrenia is warranted. It is therefore important to define a framework that will be useful to both experimental and clinical fields of study.…”
Section: Conclusion: An Updated Model Of Goal-directed Behaviors In Pmentioning
confidence: 99%
“…An understanding of the production and representations of goal‐directed behavior allows an integrative perspective on the various deficits encountered in people with schizophrenia that is largely compatible with previous dimensional approaches to schizophrenic symptoms. This concept can also contribute to novel remedial methods, as some data suggest that programs focusing on goal‐directed behaviors, such as individualized Goal Management Training, can help people with schizophrenia to manage everyday issues in a sustainable manner . Thus, we believe that further investigation of goal‐directed behaviors in patients with schizophrenia is warranted.…”
Section: Conclusion: An Updated Model Of Goal‐directed Behaviors In Pmentioning
confidence: 99%